Preparation method and application of a semi-aromatic polyimide / polyetherimide all-organic composite film

CN122878602APending Publication Date: 2026-10-09HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611295850.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]本发明的目的是为了解决传统的复合薄膜不能兼具高介电常数与高击穿电场的问题,而提供一种半芳香族聚酰亚胺/聚醚酰亚胺全有机复合薄膜的制备方法及应用

Benefits of technology

[0016](1)为了平衡静电储能介质在相对介电常数与击穿电场间的固有矛盾,引入功能型有机填料成为优化其储能性能的有效途径。本发明开发一种由宽带隙、高偶极矩单体缩聚而成的半芳香族聚酰亚胺,将其作为功能型填料引入聚醚酰亚胺中。一方面,得益于半芳香族聚酰亚胺的电荷分离特性与固有的高偶极矩官能团,使复合材料表现出更高的介电常数,从而提高材料的储能密度;另一方面,半芳香族聚酰亚胺具有宽能带的特征,能够与基体在两相界面处构筑局部势垒来抑制载流子的运输,在降低泄漏电流密度的同时提高充放电效率。此外,全有机体系避免了无机填料带来的界面缺陷,保证了材料内部的均一性,实现了所得聚醚酰亚胺复合薄膜兼具优异的绝缘性能与储能性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878602A_ABST
    Figure CN122878602A_ABST
Patent Text Reader

Abstract

The application relates to a preparation method and application of a semi-aromatic polyimide / polyetherimide all-organic composite film and relates to the technical field of energy storage materials. The application aims to solve the problem that a traditional composite film cannot have high dielectric constant and high breakdown electric field. The method is as follows: m-phenylenediamine is added into N,N-dimethylacetamide, stirring is conducted until the m-phenylenediamine is fully dissolved, 4,4'-(4,4'-isopropyl diphenyloxy) diphthalic anhydride is added, stirring is conducted until the mixture is fully stirred, a mixed solution a is obtained, N,N-dimethylacetamide is added into the mixed solution a, semi-aromatic polyimide is added, stirring is conducted until the mixture is fully mixed, a mixed solution b is obtained, the mixed solution b is vacuumized, is coated on a pretreated substrate, gradient temperature curing is conducted, and the film on the substrate is peeled off. The application can obtain a preparation method and application of a semi-aromatic polyimide / polyetherimide allorganic composite film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of energy storage materials technology, specifically to a method for preparing and applying a semi-aromatic polyimide / polyetherimide all-organic composite thin film. Background Technology

[0002] With the rapid development of the new energy equipment industry, high-energy-storage components have become core supporting parts for ensuring the efficient and stable operation of electrical systems. Compared with batteries and electrochemical capacitors, electrostatic capacitors play a vital role in various advanced technology fields due to their advantages of high power density and purely physical charge-discharge characteristics.

[0003] The dielectric materials in electrostatic capacitors are mainly divided into inorganic dielectrics and organic dielectrics. Among them, polymer dielectric films are considered to be materials with great application potential in the field of electrostatic energy storage due to their excellent insulation and mechanical properties. However, the energy storage performance of the material is affected by the inherent constraints of the relative permittivity and the breakdown electric field; at the same time, the carrier surge phenomenon caused by high temperature will further cause a large amount of energy loss, limiting its practical application in extreme environments.

[0004] Dispersing wide-bandgap inorganic materials as functional fillers in polymer matrices, or coating such inorganic materials on polymer surfaces to construct inorganic barrier layers, can improve the dielectric constant while suppressing carrier transport or injection, thus improving the energy storage performance of materials to some extent. However, in the preparation of inorganic / organic composite materials, the significant differences in the intrinsic properties of the two phases often lead to problems such as easy generation of interface defects, difficulty in dispersing inorganic nanoparticles, and high process complexity during the preparation of composite films. This makes them unsuitable for the needs of large-scale industrial production. Summary of the Invention

[0005] The purpose of this invention is to solve the problem that traditional composite films cannot simultaneously possess both high dielectric constant and high breakdown electric field, and to provide a method for preparing and applying a semi-aromatic polyimide / polyetherimide all-organic composite film.

[0006] A method for preparing a semi-aromatic polyimide / polyetherimide all-organic composite film, comprising the following steps:

[0007] Step S1: Preparation of functionalized semi-aromatic polyimide;

[0008] Dicyclohexyl-3,4,3',4'-tetracarboxylic dianhydride and sulfamic acid were dissolved in m-cresol, and then a catalyst was added. The mixture was stirred thoroughly under a nitrogen atmosphere at 90-100°C, and then the temperature was raised to 180-190°C and the reaction was continued with stirring. After the reaction was completed, the reaction solution was precipitated, filtered, and washed to obtain a semi-aromatic polyimide.

[0009] Step S2: Prepare polyetherimide acid solution;

[0010] Add m-phenylenediamine to N,N-dimethylacetamide and stir until the m-phenylenediamine is fully dissolved. Then add 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride and stir thoroughly to obtain mixed solution a.

[0011] Step S3: Prepare a semi-aromatic polyimide / polyetherimide film;

[0012] N,N-dimethylacetamide was added to the mixed solution a obtained in step S2, and then the semi-aromatic polyimide obtained in step S1 was added. After stirring until completely mixed, mixed solution b was obtained. Mixed solution b was vacuumed and then coated onto a pretreated substrate. After gradient temperature curing, the film on the substrate was peeled off to obtain a semi-aromatic polyimide / polyetherimide all-organic composite film.

[0013] The semi-aromatic polyimide comprises 4%, 8%, 12%, or 16% of the total mass of the semi-aromatic polyimide, 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride, and m-phenylenediamine.

[0014] Application of a semi-aromatic polyimide / polyetherimide all-organic composite film, specifically its application in high-temperature energy storage capacitors.

[0015] The beneficial effects of this invention are:

[0016] (1) To balance the inherent contradiction between the relative permittivity and breakdown electric field of electrostatic energy storage media, introducing functional organic fillers has become an effective way to optimize their energy storage performance. This invention develops a semi-aromatic polyimide formed by the condensation polymerization of a wide-bandgap, high-dipole-moment monomer, and introduces it as a functional filler into polyetherimide. On the one hand, thanks to the charge separation characteristics and inherent high-dipole-moment functional groups of the semi-aromatic polyimide, the composite material exhibits a higher dielectric constant, thereby improving the energy storage density of the material; on the other hand, the semi-aromatic polyimide has a wide bandgap characteristic, which can build a local barrier with the matrix at the two-phase interface to suppress the transport of charge carriers, thereby reducing the leakage current density and improving the charge and discharge efficiency. In addition, the all-organic system avoids the interface defects caused by inorganic fillers, ensures the uniformity of the material, and realizes that the obtained polyetherimide composite film has both excellent insulation and energy storage performance.

[0017] (2) This invention provides a method for preparing a semi-aromatic polyimide / polyetherimide all-organic composite dielectric film, and the resulting dielectric material can be widely used in advanced fields such as electrical, electronic and new energy vehicles.

[0018] This invention provides a method for preparing a semi-aromatic polyimide / polyetherimide all-organic composite film and its application. Attached Figure Description

[0019] Figure 1 Fourier transform infrared spectrum of semi-aromatic polyimide;

[0020] Figure 2 The Fourier transform infrared spectra of the thin film materials in Examples 1-4 and Comparative Example 1 are shown.

[0021] Figure 3 The X-ray diffraction patterns of the thin film materials in Examples 1-4 and Comparative Example 1 are shown.

[0022] Figure 4 The differential scanning calorimetry (DSC) curves of the thin film materials in Examples 1-4 and Comparative Example 1 are shown.

[0023] Figure 5 This shows scanning electron microscope images of the thin film materials in Examples 1-4 and Comparative Example 1;

[0024] Figure 6 The graph shows the variation of dielectric constant and dielectric loss of the thin film materials in Examples 1-4 and Comparative Example 1 at 150°C with frequency.

[0025] Figure 7 The graph shows the variation of dielectric constant and dielectric loss of the thin film materials in Examples 1-4 and Comparative Example 1 at 200°C with frequency.

[0026] Figure 8 This shows the breakdown field strength spectra of the thin film materials in Examples 1-4 and Comparative Example 1 at 150°C.

[0027] Figure 9 This shows the breakdown field strength spectra of the thin film materials in Examples 1-4 and Comparative Example 1 at 200°C;

[0028] Figure 10 The leakage current density-electric field intensity curves of the thin film materials in Examples 1-4 and Comparative Example 1 at 150°C are shown.

[0029] Figure 11 This shows the leakage current density-electric field intensity curves of the thin film materials in Examples 1-4 and Comparative Example 1 at 200°C;

[0030] Figure 12 This shows the energy storage density curves of the thin film materials in Examples 1-4 and Comparative Example 1 at 150°C;

[0031] Figure 13 This shows the energy storage density curves of the thin film materials in Examples 1-4 and Comparative Example 1 at 200°C;

[0032] Figure 14 This shows the cyclic test diagrams of the thin film materials in Examples 1-4 and Comparative Example 1;

[0033] Figure 15 The stress-strain curves of the thin film materials in Examples 1-4 and Comparative Example 1 at 25°C are shown. Detailed Implementation

[0034] Specific Implementation Method 1: This implementation method describes a method for preparing a semi-aromatic polyimide / polyetherimide all-organic composite film, which is carried out according to the following steps:

[0035] Step S1: Preparation of functionalized semi-aromatic polyimide;

[0036] Dicyclohexyl-3,4,3',4'-tetracarboxylic dianhydride and sulfamic acid were dissolved in m-cresol, and then a catalyst was added. The mixture was stirred thoroughly under a nitrogen atmosphere at 90-100°C, and then the temperature was raised to 180-190°C and the reaction was continued with stirring. After the reaction was completed, the reaction solution was precipitated, filtered, and washed to obtain a semi-aromatic polyimide.

[0037] Step S2: Prepare polyetherimide acid solution;

[0038] Add m-phenylenediamine to N,N-dimethylacetamide and stir until the m-phenylenediamine is fully dissolved. Then add 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride and stir thoroughly to obtain mixed solution a.

[0039] Step S3: Prepare a semi-aromatic polyimide / polyetherimide film;

[0040] N,N-dimethylacetamide was added to the mixed solution a obtained in step S2, and then the semi-aromatic polyimide obtained in step S1 was added. After stirring until completely mixed, mixed solution b was obtained. Mixed solution b was vacuumed and then coated onto a pretreated substrate. After gradient temperature curing, the film on the substrate was peeled off to obtain a semi-aromatic polyimide / polyetherimide all-organic composite film.

[0041] The semi-aromatic polyimide comprises 4%, 8%, 12%, or 16% of the total mass of the semi-aromatic polyimide, 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride, and m-phenylenediamine.

[0042] Specific Implementation Method Two: The difference between this implementation method and Specific Implementation Method One is that the ratio of the mass of dicyclohexyl-3,4,3',4'-tetracarboxylic dianhydride, the mass of sulfamic acid, the mass of the catalyst, and the volume of m-cresol in step S1 is (5.7~5.8) g : (4.6~4.7) g : (1.20~1.25) g : (40~42) mL.

[0043] The other steps are the same as in Specific Implementation Method 1.

[0044] Specific Implementation Method 3: The difference between this implementation method and Specific Implementation Method 1 or 2 is that the catalyst is isoquinoline.

[0045] The other steps are the same as in Specific Implementation Method 1 or 2.

[0046] Specific Implementation Method Four: The difference between this implementation method and Specific Implementation Methods One to Three is that the reaction time at 90~100℃ in step S1 is 7~9h, and the reaction time at 180~190℃ is 7~9h.

[0047] The other steps are the same as those in Specific Implementation Methods One to Three.

[0048] Specific Implementation Method 5: The difference between this implementation method and Specific Implementation Methods 1 to 4 is that the ratio of the mass of m-phenylenediamine, the mass of 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride, and the volume of N,N-dimethylacetamide in step S2 is (0.41~0.43) g : (2.23~2.31) g : (10~11) mL.

[0049] The other steps are the same as those in Specific Implementation Methods One through Four.

[0050] Specific Implementation Method Six: The difference between this implementation method and Specific Implementation Methods One to Five is that the stirring time in step S2 is 30~40 minutes.

[0051] The other steps are the same as those in Specific Implementation Methods 1 to 5.

[0052] Specific Implementation Method Seven: The difference between this implementation method and Specific Implementation Methods One to Six is ​​that a mechanical stirrer is used in steps S1, S2 and S3, and the stirring speed is 250~300r / min.

[0053] The other steps are the same as those in Specific Implementation Methods 1 to 6.

[0054] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Methods One through Seven in that the substrate described in step S3 is processed according to the following steps:

[0055] First, the substrate is soaked in N,N-dimethylacetamide solution for 1-2 hours, then washed 2-3 times with anhydrous ethanol, and then dried at 60-70°C for 9-10 hours to obtain a pretreated substrate, wherein the substrate is a glass plate.

[0056] The other steps are the same as those in Specific Implementation Methods 1 to 7.

[0057] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods One to Eight in that the gradient temperature curing described in step S3 is performed according to the following steps:

[0058] First, keep it at 80~85℃ for 6~7 hours, then keep it at 105~115℃, 135~145℃, 165~175℃, 195~205℃ and 225~235℃ for 0.5~0.75 hours in sequence, and finally keep it at 265~275℃ for 0.75~1 hour.

[0059] The other steps are the same as those in Specific Implementation Methods 1 to 8.

[0060] Specific Implementation Method 10: This implementation method describes the application of a semi-aromatic polyimide / polyetherimide all-organic composite film, specifically its application in high-temperature energy storage capacitors.

[0061] The beneficial effects of the present invention are verified using the following embodiments:

[0062] Example 1: A method for preparing a semi-aromatic polyimide / polyetherimide all-organic composite film, comprising the following steps:

[0063] Step S1: Preparation of functionalized semi-aromatic polyimide;

[0064] 5.7 g of dicyclohexyl-3,4,3',4'-tetracarboxylic dianhydride and 4.6 g of aminophenyl sulfone were dissolved in 40 mL of m-cresol, and then 1.2 g of isoquinoline catalyst was added. The mixture was stirred at 90 °C for 8 h under a nitrogen atmosphere, and then heated to 180 °C and stirred for another 8 h. After the reaction was completed, the reaction solution was precipitated in anhydrous ethanol while hot, filtered, and washed to obtain a white powder, which is the semi-aromatic polyimide.

[0065] Step S2: Prepare polyetherimide acid solution;

[0066] In a three-necked flask, 0.41 g of m-phenylenediamine was dissolved in 10 mL of N,N-dimethylacetamide. After stirring until the m-phenylenediamine was fully dissolved, 2.23 g of 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride was gradually added. After stirring for 35 min until viscous, mixed solution a was obtained.

[0067] Step S3: Prepare a semi-aromatic polyimide / polyetherimide film;

[0068] The substrate was first soaked in N,N-dimethylacetamide solution for 1 hour, then washed three times with anhydrous ethanol, and then dried at 60°C for 10 hours to obtain a pretreated substrate, wherein the substrate is a glass plate.

[0069] N,N-dimethylacetamide was added to the mixed solution a obtained in step S2, and then the semi-aromatic polyimide obtained in step S1 was added. After stirring until completely mixed, mixed solution b was obtained. Mixed solution b was vacuumed and then coated onto a pretreated substrate. It was first kept at 80°C for 6 hours, then kept at 110°C, 140°C, 170°C, 200°C and 230°C for 0.5 hours in sequence, and finally kept at 270°C for 1 hour. The film on the substrate was then peeled off to obtain a semi-aromatic polyimide / polyetherimide all-organic composite film.

[0070] A mechanical stirrer is used in steps S1, S2 and S3, and the stirring speed is 300 r / min.

[0071] The semi-aromatic polyimide comprises 4% of the total mass of the semi-aromatic polyimide, 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride, and m-phenylenediamine.

[0072] Example 2: In this example, the semi-aromatic polyimide accounts for 8% of the total mass of the semi-aromatic polyimide, 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride and m-phenylenediamine; other experimental conditions are the same as in Example 1.

[0073] Example 3: In this example, the semi-aromatic polyimide accounts for 12% of the total mass of the semi-aromatic polyimide, 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride and m-phenylenediamine; other experimental conditions are the same as in Example 1.

[0074] Example 4: In this example, the semi-aromatic polyimide accounts for 16% of the total mass of the semi-aromatic polyimide, 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride and m-phenylenediamine; other experimental conditions are the same as in Example 1.

[0075] Comparative Example 1: No semi-aromatic polyimide was added in this comparative example; all other experimental conditions were the same as in Example 1.

[0076] Figure 1 Represents the Fourier transform infrared spectrum of semi-aromatic polyimides; such as Figure 1 As shown, 1156cm -1 1296cm -1 These are the characteristic peaks of the symmetric and asymmetric stretching vibrations at S=O, respectively; 1717 cm⁻¹ -1 1785cm -1 These are the characteristic peaks of the symmetric and asymmetric stretching vibrations of C=O, respectively; 1369 cm⁻¹ -1 The characteristic peak of the stretching vibration corresponding to CN at this location proves that the semi-aromatic polyimide was successfully synthesized.

[0077] Figure 2The Fourier transform infrared spectra of the thin film materials in Examples 1-4 and Comparative Example 1 are shown; Figure 2 As shown, each dielectric film exhibits typical imide C=O symmetric and asymmetric stretching vibration peaks, CN stretching vibration peaks, and bending vibration peaks. Specifically, at 1779 cm⁻¹... -1 1723 cm -1 The peaks at 1359 cm⁻¹ represent the characteristic peaks of the asymmetric and symmetric stretching vibrations of C=O, respectively. -1 744cm -1 The peaks at these locations represent the characteristic peaks of the stretching and bending vibrations of the CN bond, respectively. Additionally, at 1238 cm⁻¹... -1 The peak at 2970 cm⁻¹ exhibits characteristic stretching vibrations of the ether chain segment. -1 and 2873 cm -1 The material exhibits a stretching vibration peak of -CH3. The introduction of SPI did not cause any shift in the characteristic peaks of the material, indicating that no chemical reaction occurred between PEI and SPI, and the complete polyetherimide structure was maintained.

[0078] Figure 3 The X-ray diffraction patterns of the thin film materials in Examples 1-4 and Comparative Example 1 are shown; Figure 3 As shown, the X-ray diffraction curves of the semi-aromatic polyimide / polyetherimide composite material did not change significantly compared with pure polyetherimide. Both exhibited broad diffraction dispersion peaks at 2θ≈23°, indicating that the introduction of semi-aromatic polyimide did not destroy the phase structure of polyetherimide, and all dielectric films maintained amorphous properties.

[0079] Figure 4 The differential scanning calorimetry (DSC) curves of the thin film materials in Examples 1-4 and Comparative Example 1 are shown; Figure 4 As shown, the glass transition temperatures of all materials remain within the range of 210-215℃, indicating that they maintain a glassy state within the temperature range of 25℃ to 200℃ and have good thermal stability.

[0080] Figure 5 The images show scanning electron microscope (SEM) images of the thin film materials in Examples 1-4 and Comparative Example 1; as shown. Figure 5 As shown, there are no obvious pores or cracks on the material surface. This confirms that the composite film has a continuous and uniform film structure, without obvious phase separation or filler agglomeration, effectively avoiding the defects caused by poor interfacial compatibility and uneven dispersion in traditional inorganic filler / polyetherimide composite systems, thus providing a structural basis for excellent electrical insulation performance.

[0081] Figure 6 This diagram illustrates the variation of dielectric constant and dielectric loss of the thin film materials in Examples 1-4 and Comparative Example 1 at 150°C with frequency. Figure 7The graph shows the variation of dielectric constant and dielectric loss of the thin film materials in Examples 1-4 and Comparative Example 1 at 200°C with frequency. Figure 6-7 As shown, at various temperatures, the dielectric constant of the materials increases with the increase of the semi-aromatic polyimide content, and the increase in dielectric constant is beneficial to improving the energy storage performance of the dielectric film. The dielectric constant of each film at different temperatures decreases slightly with increasing frequency. This is because the dipolarization lags behind the change in electric field, causing the dipole polarization intensity to gradually decrease, ultimately leading to a decrease in dielectric constant. In addition, the dielectric loss of all materials increases slightly due to the influence of relaxation loss; however, the dielectric loss remains at a low level (<0.01) at all temperatures, indicating that the composite film has good dielectric stability.

[0082] Figure 8 This shows the breakdown field strength spectra of the thin film materials in Examples 1-4 and Comparative Example 1 at 150°C. Figure 9 The diagram shows the breakdown field strength spectra of the thin film materials in Examples 1-4 and Comparative Example 1 at 200°C. Figure 8-9 As shown in the figure, the Weibull distribution curves of DC breakdown strength for pure polyetherimide and the composite film at 150℃ and 200℃ are presented respectively. It can be seen that at the high-temperature test temperatures, the breakdown behavior of each sample conforms well to the Weibull statistical law, indicating that the test results have good repeatability and statistical reliability. Compared with pure polyetherimide, the semi-aromatic polyimide / polyetherimide composite film exhibits higher breakdown strength, indicating that the functional semi-aromatic polyimide has a significant enhancing effect on the electrical insulation properties of polyetherimide.

[0083] Figure 10 This shows the leakage current density-electric field intensity curves of the thin film materials in Examples 1-4 and Comparative Example 1 at 150°C. Figure 11 The diagram shows the leakage current density-electric field intensity curves of the thin film materials in Examples 1-4 and Comparative Example 1 at 200°C. When polymer thin films operate under high-temperature conditions, conduction losses caused by leakage current are the main source of loss. To analyze the variation of conduction losses in dielectric thin films at high temperatures, the leakage current of each dielectric material was tested at high temperatures, and the leakage current density-electric field intensity curves were obtained. For example... Figure 10-11 As shown, the leakage current density of all dielectric films increases with increasing temperature. This is because high temperature reduces the energy of carrier transitions, making carriers more likely to move. The introduction of semi-aromatic polyimide can reduce the leakage current density of the dielectric film to varying degrees. The variation of leakage current density at different temperatures shows a similar trend, with Example 3 exhibiting the lowest leakage current density. For example, at 200°C, the leakage current density of Example 3 is 3.94 × 10⁻⁶. -8 A / cm 2Compared to pure polyetherimide film under the same conditions (1.30 × 10⁻⁶), -7 A / cm 2 It decreased by an order of magnitude.

[0084] Figure 12 This shows the energy storage density curves of the thin film materials in Examples 1-4 and Comparative Example 1 at 150°C. Figure 13 The energy storage density curves of the thin film materials in Examples 1-4 and Comparative Example 1 at 200°C are shown. Figure 12-13 As shown, at 150°C, the discharge energy density of Example 3 reached 5.03 J / cm³. 3 It is pure polyetherimide (2.21 J / cm). 3 The discharge energy density of Example 3 reached 2.31 J / cm³, which is 2.28 times that of Example 3, with a charge / discharge efficiency of 90.1%. At a higher temperature of 200°C, the discharge energy density of Example 3 reached 2.31 J / cm³. 3 It is pure polyetherimide (1.25 J / cm). 3 The efficiency of the semi-aromatic polyimide is 1.85 times that of the standard polyimide, and the charge-discharge efficiency reaches 91.5%. The above results prove that the introduction of semi-aromatic polyimide can effectively reduce the leakage current density of the dielectric film under high temperature and high electric field and prevent it from developing into a breakdown current, so that the composite dielectric film has excellent energy storage performance under extreme conditions; however, the introduction of too much semi-aromatic polyimide will lead to a decrease in insulation performance, thereby deteriorating the energy storage performance.

[0085] Figure 14 This shows the cyclic test graphs of the thin film materials in Examples 1-4 and Comparative Example 1; as shown. Figure 14 As shown, under conditions of 200℃ and 200 MV / m, the discharge energy density and charge-discharge efficiency of Example 3 remained stable after 50,000 cycles, confirming that the composite dielectric film has excellent fatigue resistance at high temperatures.

[0086] Figure 15 The stress-strain curves of the thin film materials in Examples 1-4 and Comparative Example 1 at 25°C are shown; Figure 15 As shown, the tensile strength of each material remained at around 90 MPa, indicating that the introduction of semi-aromatic polyimide did not have a negative impact on the mechanical properties of polyetherimide.

Claims

1. A method for preparing a semi-aromatic polyimide / polyetherimide all-organic composite film, characterized in that, The preparation method is carried out according to the following steps: Step S1: Preparation of functionalized semi-aromatic polyimide; Dicyclohexyl-3,4,3',4'-tetracarboxylic dianhydride and sulfamic acid were dissolved in m-cresol, and then a catalyst was added. The mixture was stirred thoroughly under a nitrogen atmosphere at 90-100°C, and then the temperature was raised to 180-190°C and the reaction was continued with stirring. After the reaction was completed, the reaction solution was precipitated, filtered, and washed to obtain a semi-aromatic polyimide. Step S2: Prepare polyetherimide acid solution; Add m-phenylenediamine to N,N-dimethylacetamide and stir until the m-phenylenediamine is fully dissolved. Then add 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride and stir thoroughly to obtain mixed solution a. Step S3: Prepare a semi-aromatic polyimide / polyetherimide film; N,N-dimethylacetamide was added to the mixed solution a obtained in step S2, and then the semi-aromatic polyimide obtained in step S1 was added. After stirring until completely mixed, mixed solution b was obtained. Mixed solution b was vacuumed and then coated onto a pretreated substrate. After gradient temperature curing, the film on the substrate was peeled off to obtain a semi-aromatic polyimide / polyetherimide all-organic composite film. The semi-aromatic polyimide comprises 4%, 8%, 12%, or 16% of the total mass of the semi-aromatic polyimide, 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride, and m-phenylenediamine.

2. The method for preparing a semi-aromatic polyimide / polyetherimide all-organic composite film according to claim 1, characterized in that, The ratio of the mass of dicyclohexyl-3,4,3',4'-tetracarboxylic dianhydride, the mass of sulfamic acid, the mass of the catalyst, and the volume of m-cresol in step S1 is (5.7~5.8) g : (4.6~4.7) g : (1.20~1.25) g : (40~42) mL.

3. The method for preparing a semi-aromatic polyimide / polyetherimide all-organic composite film according to claim 1 or 2, characterized in that, The catalyst is isoquinoline.

4. The method for preparing a semi-aromatic polyimide / polyetherimide all-organic composite film according to claim 1, characterized in that, In step S1, the reaction time at 90~100℃ is 7~9h, and the reaction time at 180~190℃ is 7~9h.

5. The method for preparing a semi-aromatic polyimide / polyetherimide all-organic composite film according to claim 1, characterized in that, The ratio of the mass of m-phenylenediamine, the mass of 4,4'-(4,4'-isopropyldiphenoxy)phthalic anhydride, and the volume of N,N-dimethylacetamide in step S2 is (0.41~0.43) g : (2.23~2.31) g : (10~11) mL.

6. The method for preparing a semi-aromatic polyimide / polyetherimide all-organic composite film according to claim 1, characterized in that, The stirring time in step S2 is 30~40 minutes.

7. The method for preparing a semi-aromatic polyimide / polyetherimide all-organic composite film according to claim 1, characterized in that, Mechanical stirrers are used in steps S1, S2 and S3, with a stirring rate of 250~300 r / min.

8. The method for preparing a semi-aromatic polyimide / polyetherimide all-organic composite film according to claim 1, characterized in that, The substrate described in step S3 is processed according to the following steps: The substrate is first soaked in N,N-dimethylacetamide solution for 1-2 hours, then washed 2-3 times with anhydrous ethanol, and then dried at 60-70°C for 9-10 hours to obtain a pretreated substrate, wherein the substrate is a glass plate.

9. The method for preparing a semi-aromatic polyimide / polyetherimide all-organic composite film according to claim 1, characterized in that, The gradient temperature curing described in step S3 is performed according to the following steps: First, keep it at 80~85℃ for 6~7 hours, then keep it at 105~115℃, 135~145℃, 165~175℃, 195~205℃ and 225~235℃ for 0.5~0.75 hours in sequence, and finally keep it at 265~275℃ for 0.75~1 hour.

10. The application of a semi-aromatic polyimide / polyetherimide all-organic composite film prepared by the method according to any one of claims 1-9, characterized in that, The application of the semi-aromatic polyimide / polyetherimide all-organic composite film in high-temperature energy storage capacitors.